2001
DOI: 10.1037/0894-4105.15.2.244
|View full text |Cite
|
Sign up to set email alerts
|

Latent inhibition with a response time measure from a within-subject design: Effects of number of preexposures, masking task, context change, and delay.

Abstract: Latent inhibition (LI), poorer performance on a learning task to a previously irrelevant stimulus than to a novel stimulus, was produced in 4 experiments, using a within-subject design and a response time (RT) measure. LI was reduced by decreasing the number of stimulus preexposures, omitting the masking task, changing the context from the preexposure to the test phase, and introducing a delay between the 2 phases. Together, these effects indicate that the within-subject RT-based LI reflects the same processes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
24
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 47 publications
3
24
0
Order By: Relevance
“…The procedure employed in the current study was the recently developed and validated within-participants reaction time LI procedure (De la Casa & Lubow, 2001), with each participant being presented with both non-preexposed (NPE) and preexposed (PE) stimuli. All the participants were positioned approximately 50 cm from the computer screen, with a response pad positioned to either the left-or right-hand side of the computer, depending on which was the dominant hand.…”
Section: Latent Inhibition-preexposure Phasementioning
confidence: 99%
“…The procedure employed in the current study was the recently developed and validated within-participants reaction time LI procedure (De la Casa & Lubow, 2001), with each participant being presented with both non-preexposed (NPE) and preexposed (PE) stimuli. All the participants were positioned approximately 50 cm from the computer screen, with a response pad positioned to either the left-or right-hand side of the computer, depending on which was the dominant hand.…”
Section: Latent Inhibition-preexposure Phasementioning
confidence: 99%
“…There is, however, growing evidence on the non-trials-tocriterion tasks that LI is a function of the amount of pre-exposure, for example, Lipp, Siddle, and Vaitl (1992) demonstrated that LI was enhanced with increased numbers of pre-exposure on a Pavlovian conditioning task, using autonomic responses as the dependent variable. De la Casa and Lubow (2001) also demonstrated that LI is a function of numbers of pre-exposure on a new within-subject reaction time-based task, with LI established with 30 PEs, but not with 3 or 5 PEs. This, therefore, raises the question of whether the trials-to-criterion LI tasks do actually represent the same psychological process as in animal LI, or indeed as Lipp (1999) suggests, as in human Pavlovian conditioning of autonomic responses.…”
mentioning
confidence: 92%
“…Considering these limitations, these findings seem to be consistent with previous studies in which different contextual cues have been used. For example, latent inhibition was reduced in a study in which external cues (and other variables such as the number of stimulus preexposures) were changed between preexposure and testing (De la Casa & Lubow, 2001), indicating that latent inhibition is sensitive to contextual changes in different stages of the experimental procedure. In the CTA paradigm, latent inhibition attenuation after an external context change between preexposure and conditioning/testing, but not between pre-exposure/conditioning and testing, also has been described (Quintero et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the PE-D subgroups had a shorter delay compared with the PE-S subgroups, which could influence the results. Nevertheless, because greater temporal proximity between preexposure and conditioning should strengthen the effect of preexposures (De la Casa & Lubow, 2001), greater latent inhibition should be expected in the Bdifferent^sub-groups. The results indicate, however, that the subgroup with greater temporal proximity between preexposure and conditioning (PE-D subgroup) showed a disruption of latent inhibition.…”
Section: Discussionmentioning
confidence: 99%